THE IMPLEMENTATION OF ARTICLE 47 GENEVA CONVENTION I TO THE MILITARY (AN OVERVIEW OF CHALLENGES WITHIN THE INDONESIAN ARMED FORCES) - Fadillah Agus (Padjadjaran Journal of International Law, 2017)
Abstract The preferable implementation of article 47 of the First Geneva Convention 1949 is conducting activities in the format of military training and exercises rather than seminars. The contents, methodology as well as the instructor should be in accordance with military operations that will be encountered by the soldiers. “do what you have trained and train what you will do”. The implementation of article 47 GC I is related to article 82 and 87 AP I. Furthermore, within Tentara Nasional Indonesia (TNI) it is related with the formation of “the professional soldier” as enshrined in Article 2 section (4) of the Law No. 34 of 2004 of TNI. In addition to the increased awareness, some additional achievements related to operational and training aspects were also achieved in the period of 1998 – 2015. These include the issuance of Technical Guidance on the Implementation of international humanitarian law and human rights into the Training, the three standing ROEs and the TNI Commander decree on Prohibition of Torture. These all doctrinal impact are resulting from the dissemination program that may have influence on the betterment of the TNI operations in the future. However, some further improvements are required, among others, to improve the skills of the concerned officers to draft appropriate ROEs and to complement the legal unit with an operational law / international humanitarian law section. Moreover, the challenge for Indonesia in the future is to improve its enforcement mechanisms i.e. to enhance the military justice system to be more reliable and independent in line with the spirit of article 49 GC I. Keywords: international humanitarian law, armed conflict, military academy, dissemination program, laws of war. Abstrak Pelaksanaan Pasal 47 dalam Konvensi Genewa Pertama 1949 adalah melaksanakan aktivitas dalam format aktivitas pelatihan dan militer dibandingkan dengan melakukan seminar. Isi dari pelatihan, metodologi dan instruktur harus sesuai dengan operasi militer yang dihadapi oleh seorang prajurit, “lakukanlah apa yang telah dilatihkan kepadamu dan latihlahlah apa yang akan kamu lakukan”. Pelaksanaan pasal 47 Konvensi Genewa Pertama 1949 berkaitan dengan Pasal 82 dan 87 dari Konvensi yang sama. Lebih lanjut lagi, dalam Tentara Nasional Indonesia (TNI), berkaitan dengan pembentukan “prajurit profesional” seperti yang disampaikan dalam Pasal 2 ayat (4) Undang-undang No. 34 tahun 2004 mengenai TNI. Dalam rangka untuk meningkatkan kewaspadaan, beberapa capaian tambahan berkenaan dengan aspek operasional dan pelatihan juga dicapai dalam periode 1998-2015. Hal ini termasuk mengeluarkan Panduan Teknis mengenai Implementasi Hukum Humaniter Internasional dan HAM dalam pelatihan, dan tiga pilar ROEs dan keputusan Panglima TNI tentang Larangan Penyiksaan. Semua doktrin ini lahir dari dampak diseminasi dalam program pelatihan untuk melahirkan prajurit TNI yang lebih baik dimasa yang akan datang. Meskipun demikian, sejumlah peningkatan terhadap pengetahuan mengenai hukum humaniter telah tumbuh dikalangan prajutit TNI. Tantangan selanjutnya adalah mendorong peningkatan mekanisme pentaatan, misalnya mendorong sistem pengadilan militer untuk lebih indeoenden dan dapat diandalkan sejalan dengan semangat Pasal 49 Konvensi Genewa Pertama 1949. Kata kunci: hukum humaniter, konflik bersenjata, akademi militer, program diseminasi, hukum perang.